Tobacco or Health? Physiological and Social Damages Caused by Tobacco Smoking - Haustein, Knut-Olaf.; Groneberg, David; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
This book presents a summary of the consequences that tobacco smoking has on health, taking into account all organ systems affected, such as the respiratory tract, cardiovascular system, central nervous system, and urinary tract, including mineral metabolism, the pregnant woman, etc. It also describes primary prevention measures as well as possible intervention modalities, established on evidence-based medicine, to help individuals stop smoking. The book is of a high scientific standard and thus differs from many popular-science treatises. It helps inform the reader of all smoking-related problems.
History of Tobacco -- Epidemiology of Tobacco Dependence -- Tobacco Constituents and Additives -- Pharmacology and Pharmacokinetics of Nicotine -- Smoking and Lung Disease -- Cardiovascular Disease, Disturbances of Blood Coagulation and Fibrinolysis -- Other Organ Systems -- Smoking and Pregnancy -- Passive Smoking -- Non-Drug Treatments to Promote Smoking Cessation -- Pharmacotherapy of Nicotine Dependence -- Primary Prevention -- Tobacco Industry, Advertising and Advertising Bans -- Society, Politics and the Tobacco Industry -- Appendix: Experiences from a Smoker Counselling Centre.
Keywords: Medicine; Family medicine; Internal medicine; Pneumology; Oncology; Medicine & Public Health; General Practice / Family Medicine; Internal Medicine; Pneumology/Respiratory System; Oncology